ANALISIS EFEKTIFITAS PENGENDALIAN INTERNAL KOPERASI SIMPAN PINJAM DAN UNIT SIMPAN PINJAM (STUDI KASUS PADA EMPAT BUAH KOPERASI DI WILAYAH KABUPATEN SLEMAN) - , NIKITA SANGMARKA ING ENDIT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research analyzes the effectiveness of the implementation internal control in credit unions and savings and loans unit that are in the district of Sleman. Internal control theory used based on the theory internal control of The Committee of Sponsoring Organizations (COSO, 1992). Elements of internal control used is the control environment, risk assessment, control activities, information and communication and monitoring. Cooperative as a business entity that should always be directed and encouraged to join and participate substantially in improving the revenue and welfare of its members in order to overcome economic and social inequality. So expect able to participate as a forum for cooperative economic activities of the people are independent and free of the parties that could hinder the achievement of the cooperative. With the analysis of the effectiveness of the the implementation internal control unit credit unions and savings and loans, the cooperative was able to see the advantages and disadvantages of the implementation internal control for credit unions and savings and loan unit.